Enhancing bioactive compounds and antioxidant properties: role of germination in rice. - Preecharram, S.; Poomsuk, N.; Thummavongsa, T.; Posoongnoen, S.; Jandaruang, J. (International Journal of Agricultural Technology, 2025)
The germination time (24, 48, 72, or 96 hours) on the protein content, protein molecular weight, GABA, phenolic compounds, and antioxidant activity in two rice varieties: Hom Mali 105 and Hom Nil were investigated. Based on the results, a germination time of 72 hours produced the highest levels of protein, GABA, phenolic compounds, and antioxidant activity in both varieties. The following were the values for Hom Mali 105 rice: protein content, 1.77 mg/100 g dry weight; protein molecular weight, 14.4–41.1 kDa; GABA, 254.81 mg/100 g dry weight; phenolic compounds, 258.73 mg/100 g dry weight; and antioxidant activity, 82.92%. The values for Hom Nil rice were protein content, 1.89 mg/100 g dry weight; protein molecular weight, 14.4–97.0 kDa; GABA, 409.79 mg/100 g dry weight; phenolic compounds, 313.59 mg/100 g dry weight; and antioxidant activity, 88.94%. These findings indicated that a germination period of 72 hours was optimal for enhancing the bioactive compound levels in germinated rice of both the Hom Mali 105 and Hom Nil varieties.